The role of market linkage in growth of micro and small scale enterprises: The case of Ambo town, Ethiopia - Obsa Ensermu Gudeta; Daniel Tadesse Tulu (Journal of Innovation and Entrepreneurship, 2022)
The research aims to investigate the roles of market linkage for the growth of MSE in Ambo town. The data were collected through questionnaires and interviews. A stratified sampling technique is used to select among the seven business sectors. Data were analyzed using descriptive and inferential statistics. The study elicited five major factors that affects the growth of MSE which include financial capacity, government support, entrepreneurial competency, marketing information, and types of business sectors. The findings from correlation and regression further indicate that there exists a positive and significant relationship between MSEs growth and, financial capacity, government support, entrepreneurial competency, marketing information, and types of business sectors. The concerned bodies should facilitate market linkage enhancement between MSE and the market. MSEs on their part are expected to improve financial capacity and competence. Furthermore, adequate market information has to be collected continuously to improve the linkage. By and general, growth of MSE is attributed to internal as well as external market linkage factors. In addition entrepreneurial competency of the person leading the enterprises is vital in creating good market linkage which in turn brings MSE growth.
Keywords: 650; Ambo; Growth; Market linkage; Micro and small scale enterprises